2017
DOI: 10.1097/brs.0000000000002139
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated With Lateral Interbody Fusion: Nationwide Survey of 2998 Cases During the First 2 Years of Its Use in Japan

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
109
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 36 publications
5
109
1
3
Order By: Relevance
“…Compared to that study, we demonstrated a further minimally invasive OLIF technique aided by tubular retractor system. Another study based on a nationwide survey in Japan [ 36 ] demonstrated that compared with extreme lateral trans-psoas interbody fusion, OLIF procedure can effectively reduce the incidence of related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to that study, we demonstrated a further minimally invasive OLIF technique aided by tubular retractor system. Another study based on a nationwide survey in Japan [ 36 ] demonstrated that compared with extreme lateral trans-psoas interbody fusion, OLIF procedure can effectively reduce the incidence of related complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, the approach-related complications were still bothering surgeons. Intraoperative neural and vascular structures injury was associated with regional anatomic features and might result in quadriceps muscle weakness, as well as groin and thigh numbness, even massive intraoperative bleeding [ 2 , 4 , 5 , 10 ]. The safety and feasibility of this approach was becoming the focus.…”
Section: Introductionmentioning
confidence: 99%
“…OLIF surgery has become popular recent years. Stand-alone procedure offer patients many benefits small incision and scar, less blood loss, less pain, less hospitalization time, faster recovery [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the complications fluctuate from 3.7%to 66.7% [1][2][3][4][5][13][14]. Shun-wu Fan reviewed 235 patients with OLIF surgery and found 22 cases of endplate damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation